2022
DOI: 10.1038/s41416-022-01742-5
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal metastases from colorectal cancer belong to Consensus Molecular Subtype 4 and are sensitised to oxaliplatin by inhibiting reducing capacity

Abstract: Background Peritoneal metastases (PM) in colorectal cancer (CRC) are associated with therapy resistance and poor survival. Oxaliplatin monotherapy is widely applied in the intraperitoneal treatment of PM, but fails to yield clinical benefit. We aimed to identify the mechanism(s) underlying PM resistance to oxaliplatin and to develop strategies overcoming such resistance. Experimental design We generated a biobank consisting of 35 primary tumour regions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 53 publications
2
36
0
Order By: Relevance
“…Together the data indicate partial loss of epithelial identity and cell-cell contact in FAP-expressing tumour cells, but no clear gain in expression of mesenchymal genes, which is in line with a 'partial EMT' [31]. We recently demonstrated that peritoneal metastases from CRC constitute an almost homogeneous entity of CMS4 tumours [18,32]. Due to the small size of individual tumour nodules, the detection of peritoneal metastases by routine imaging is extremely challenging, hampering patient selection for surgery and assessment of treatment response [33,34].…”
Section: Tumour-selective Expression Of Fap In Myofibroblasts Endothe...mentioning
confidence: 72%
See 3 more Smart Citations
“…Together the data indicate partial loss of epithelial identity and cell-cell contact in FAP-expressing tumour cells, but no clear gain in expression of mesenchymal genes, which is in line with a 'partial EMT' [31]. We recently demonstrated that peritoneal metastases from CRC constitute an almost homogeneous entity of CMS4 tumours [18,32]. Due to the small size of individual tumour nodules, the detection of peritoneal metastases by routine imaging is extremely challenging, hampering patient selection for surgery and assessment of treatment response [33,34].…”
Section: Tumour-selective Expression Of Fap In Myofibroblasts Endothe...mentioning
confidence: 72%
“…In the accompanying paper [18], we have identified peritoneal metastases as a near-homogeneous CMS4 entity within CRC. The detection of peritoneal metastases in CRC is a major clinical challenge [33,34].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Recently, we performed an extensive molecular analysis of a cohort of colorectal peritoneal metastases and the primary tumours that give rise to them. We found that these tumours form a near-homogeneous entity of Consensus Molecular Subtype 4 (CMS4) [ 17 , 18 , 19 ], a subtype that is characterized by a high content of stromal myofibroblasts [ 20 , 21 , 22 ], which express high levels of FAP, but also Platelet-Derived Growth Factor Receptor alpha (PDGFRA) and Platelet-Derived Growth Factor Receptor beta (PDGFRB). Encouraged by the success of FAPI-PET [ 15 , 16 ], we set out to study the potential value of PDGFRB-targeted molecular imaging for the detection of peritoneal metastases and, potentially, other CMS4-like stroma-rich tumour types.…”
Section: Introductionmentioning
confidence: 99%